STRATEGI PROMOSI TERHADAP KEPUTUSAN MASYARAKAT UNTUK BERASOSIASI DENGAN KOPERASI SEKUNDER USAHA HUTAN TANAMAN RAKYAT (KSU-HTR) - Tivani Emerald Dios; Febriyan Pratama Defaz (Jurnal Ekonomi dan Bisnis, 2025)
This research discusses the promotion conducted by KSU HTR in Ranah Penantian. Currently, there are 86 cooperative members from the area from several farmer groups. Not all people have joined due to the lack of promotion and information about the MHP programme and its benefits. The main promotion is done through public relations by involving community leaders. KSU HTR can invite the community to gather at the mushola and provide an explanation about the cooperative. After that, people who already understand the benefits of the cooperative convey information directly to others. Unfortunately, this promotion is only done once so the impact is less than optimal. In addition, the community's low level of education and limited access to technology are obstacles to understanding the cooperative. Land conflicts with the Suak community have also decreased the community's trust in the co- operative. Re-promotion is urgently needed to restore community trust by using simple language that is easy to understand and explaining why it is important to join the cooperative. Promotion also needs to educate the community on the benefits of the cooperative for land management and economic improvement. Through targeted promotion, KSU HTR is expected to be able to improve relations with the community and expand its business. Restored community trust will support the sustainability of the cooperative, create better forest management, and improve the welfare of the Ranah Penantian community. Eflective promotion has proven to play a major role in encouraging people to join the cooperative.